Antimicrobial Study of Newly Synthesized Lanthanide(III) Complexes of 2-[2-hydroxy-3-methoxyphenyl]-3-[2-hydroxy-3-methoxybenzylamino]-1, 2-dihydroquinazolin-4(3H)-one. (13th February 2008) - Gudasi, Kalagouda B.; Havanur, Vidyadhar C.; Patil, Siddappa A.; Patil, Basavaraj R.
Abstract : New lanthanide(III) complexes with 2-[2-hydroxy-3-methoxyphenyl]-3-[hydroxyl-3-methoxybenzylamino]-1, 2-dihydroquin-azoline-4(3H)-one (Hmpbaq) have been synthesized and characterized by elemental analysis, conductance measurements, magnetic susceptibilities, spectroscopic (IR, NMR, UV, EPR), and thermal studies. Molar conductance studies indicate 1: 1 electrolytic behavior for these complexes. IR spectra indicate that Hmpbaq acts as a tridentate ligand coordinating through carbonyl oxygen, benzyl amine nitrogen, and deprotonated phenolic oxygen. TG and DTA studies of La(III) and Pr(III) complexes indicate the presence of two coordinated water molecules. Based on these studies, the complexes have been formulated as [La(mpbaq)2 (H2 O)2 ]· NO3, where Ln = La(III), Pr(III), Nd(III), Sm(III), Eu(III), Gd(III), Th(III), Dy(III), and Y(III). The ligand, lanthanide(III) salts, and the corresponding complexes have been simultaneously screened for their antibacterial and antifungal activities and compared with the drugs in use.